2018
DOI: 10.1007/s10389-018-0931-7
|View full text |Cite
|
Sign up to set email alerts
|

Disease mapping of tuberculosis prevalence in Eastern Cape Province, South Africa

Abstract: Aim This is an applied study to investigate the association of selected socio-economic and demographic factors with the relative risk of tuberculosis (TB) prevalence in the Eastern Cape Province of South Africa and to produce disease maps for the spatial outlines of the disease in the province. Subjects and methods This is an ecological spatial study of TB prevalence in the Eastern Cape, a province in South Africa, during the year 2014. Three socio-economic indicators and three demographic factors, all calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The present study demonstrated that highest level of deprivation, concentration, and dispersion index was associated with the highest numbers of death among TB patients who are co-infected with HIV. Similar findings have been previously reported elsewhere [ 17 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study demonstrated that highest level of deprivation, concentration, and dispersion index was associated with the highest numbers of death among TB patients who are co-infected with HIV. Similar findings have been previously reported elsewhere [ 17 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that when healthcare expenditures are efficiently managed, TB cases will significantly decrease because health care providers will be trained to improve the ability to diagnose and treat persons with TB disease; there will be improvements in laboratory diagnostic methods with early testing and management of TB patients; implementation of appropriate infection prevention and control precautions in health care facilities and other congregate settings in order to reduce TB transmission rates; as well as strengthening of local health facilities and TB control programs in order to undertake monitoring and evaluation of TB patients on therapy [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the South African provincial and local government health expenditure per headcount does provide insight into equity in justice and resources distribution (6,9,10), there is therefore an urgent need for addressing TB and HIV health services integration in most deprived geographical areas in the OR Tambo district in order to curb HIV associated TB deaths. Previous studies have shown that strengthening of HIV and TB services integration plays a positive role in reducing both TB/HIV incidence and mortality among individuals living under conditions of highest deprivation-concentration-dispersion (6,15,16,20).…”
Section: Discussionmentioning
confidence: 99%
“…TB and HIV health services integration in most deprived geographical areas in the OR Tambo district in order to curb HIV associated TB deaths. Previous studies have shown that strengthening of HIV and TB services integration plays a positive role in reducing both TB/HIV incidence and mortality among individuals living under conditions of highest deprivation-concentration-dispersion(6,15,16,20).South Africa has more people living with HIV and the vast majority are on ART(8). Despite the fact that the study by Williams demonstrated that the successful roll-out of ART has been associated with a 72% reduction in the incidence of HIV among adults from 1996 to 2016 and a 74% reduction inAIDS-related mortality from 2006 to 2016 (21), integrating TB and HIV health services is thought to actually play a major role, and might substantially reduce TB/HIV mortality in South Africa by 2030 irrespective of other traditional risk factors.…”
mentioning
confidence: 99%